Prevalence of Common Alleles of Some Stress Resilience Genes among Adolescents Born in Different Periods Relative to the Socioeconomic Crisis of the 1990s in Russia - Svetlana V. Mikhailova; Dinara E. Ivanoshchuk; Evgeniy A. Yushkevich; Ahmad Bairqdar; Maksim S. Anisimenko; Liliya V. Shcherbakova; Diana V. Denisova; Pavel S. Orlov (Current Issues in Molecular Biology, 2022)
Social stress is common among people and is considered one of the causes of the declining birth rate. Predisposition to stress and stress-induced disorders is largely determined genetically. We hypothesized that due to differences in stress resistance, carriers of different genetic variants of genes associated with stress resilience and stress-induced diseases may have dissimilar numbers of offspring under conditions of long-term social stress. To test this hypothesis, a comparative analysis of frequencies of seven common polymorphic regions [exon 3 variable number of tandem repeats (VNTR) of the DRD4 gene, rs4680 of COMT, STin2 VNTR and the 5-HTTLPR (rs774676466) insertion/deletion polymorphism of SLC6A4, rs4570625 of TPH2, rs6265 of BDNF, and rs258747 of NR3C1] was performed on standardized groups of randomly selected adolescents born before, during, and after severe socioeconomic deprivation (the crisis of the 1990s in Russia). There were significant differences in frequencies of “long” alleles of the DRD4 gene (p = 0.020, χ2 = 5.492) and rs4680 (p = 0.022, χ2 = 5.289) in the “crisis” group as compared to the combined “noncrisis” population. It is possible that the dopaminergic system had an impact on the successful adaptation of a person to social stress.